Acute Relationship between Cognitive and Psychological Symptoms of Patients with Mild Traumatic Brain Injury. (4th March 2012) - de Guise, Elaine; LeBlanc, Joanne; Tinawi, Simon; Lamoureux, Julie; Feyz, Mitra
Abstract : Objective . The goal of this study was to explore the relationship between acute psychological reactions and cognition as well as postconcussive symptoms in patients with MTBI. Research Methods . Sociodemographic and medical history data were gathered for 59 patients diagnosed with MTBI. Validated and standardized tools were used to assess anxiety, depression, and cognitive function two weeks after trauma. Postconcussive symptoms were assessed with the Rivermead postconcussive questionnaire. Results . Despite the absence of significant neuropsychological deficits, a very high level of anxiety and depression was observed in our cohort. Level of anxiety and depression were positively related to cognitive performances and to postconcussive symptoms. Moreover, patients with preexisting alcohol and psychological problems were more likely to present with acute depression after MTBI. Conclusions . Early psychological rehabilitation should be provided to decrease the intensity and frequency of postconcussive symptoms and diminish the risk of these problems becoming chronic.